Retinoic acid and cAMP inhibit rat hepatocellular carcinoma cell proliferation and enhance cell differentiation - M. Ionta; M.C. Rosa; R.B. Almeida; V.M. Freitas; P. Rezende-Teixeira; G.M. Machado-Santelli (Brazilian Journal of Medical and Biological Research, 2012)
Hepatocellular carcinoma (HCC) is the third highest cause of cancer death worldwide. In general, the disease is diagnosed at an advanced stage when potentially curative therapies are no longer feasible. For this reason, it is very important to develop new therapeutic approaches. Retinoic acid (RA) is a natural derivative of vitamin A that regulates important biological processes including cell proliferation and differentiation. In vitro studies have shown that RA is effective in inhibiting growth of HCC cells; however, responsiveness to treatment varies among different HCC cell lines. The objective of the present study was to determine if the combined use of RA (0.1 µM) and cAMP (1 mM), an important second messenger, improves the responsiveness of HCC cells to RA treatment. We evaluated the proliferative behavior of an HCC cell line (HTC) and the expression profile of genes related to cancer signaling pathway (ERK and GSK-3β) and liver differentiation (E-cadherin, connexin 26 (Cx26), and Cx32). RA and cAMP were effective in inhibiting the proliferation of HTC cells independently of combined use. However, when a mixture of RA and cAMP was used, the signals concerning the degree of cell differentiation were increased. As demonstrated by Western blot, the treatment increased E-cadherin, Cx26, Cx32 and Ser9-GSK-3β (inactive form) expression while the expression of Cx43, Tyr216-GSK-3β (active form) and phosphorylated ERK decreased. Furthermore, telomerase activity was inhibited along treatment. Taken together, the results showed that the combined use of RA and cAMP is more effective in inducing differentiation of HTC cells.